Social media campaigns strategies for public relations and marketing - Kim, Carolyn Mae
"Focusing on the core principles of how social media craft reciprocal, one-to-one connections with brands, this book outlines a four-step process for developing a successful social media campaign. This new edition continues to give students a foundation in the principles of digital audience engagement and data metrics across platforms, preparing them to adapt to the quickly evolving world of digital media. It takes students through the processes of social listening, strategic design, creative engagement, and evaluation, with expert insights from social media professionals. Thoroughly updated, this second edition includes new end-of-chapter activities to guide students in the initial campaign planning phase added content on influencers and crowd-funding coverage of research evaluation, the implications of findings, and articulating the ROI expanded discussion of ethical considerations in campaign design and data collection and analysis The book is suited to both undergraduate and post-graduate students as a primary text for courses in social/digital media marketing and public relations or a secondary text in broader public relations and marketing campaign planning and writing courses. Accompanying online resources include chapter reviews with suggestions for further resources; instructor guides; in-class exercises; a sample syllabus, assignments, and exams; and lecture slides"--Provided by publisher.